To solve the quadratic equation \( x^2 = 6x + 27 \) using the factoring method, we first need to rearrange it into standard form, which is \( ax^2 + bx + c = 0 \).
- Move all terms to one side of the equation: \[ x^2 - 6x - 27 = 0 \]
Now we have the quadratic in standard form \( ax^2 + bx + c = 0 \), where \( a = 1 \), \( b = -6 \), and \( c = -27 \).
- Next, we will factor the quadratic \( x^2 - 6x - 27 \). We need to find two numbers that multiply to \( -27 \) (the constant term) and add up to \( -6 \) (the coefficient of \( x \)).
The two numbers that meet these criteria are \( -9 \) and \( 3 \) because:
- \( -9 \times 3 = -27 \)
- \( -9 + 3 = -6 \)
-
We can now factor the quadratic: \[ (x - 9)(x + 3) = 0 \]
-
To find the roots, we set each factor equal to zero: \[ x - 9 = 0 \quad \Rightarrow \quad x = 9 \] \[ x + 3 = 0 \quad \Rightarrow \quad x = -3 \]
-
The roots of the equation are: \[ x = 9, -3 \]
Thus, the final answer is: \[ \boxed{9, -3} \]